A Study of Customer Relationship Management in Malaysian Commercial Banks and Its Implications for the Small and Medium Enterprises - Thangarajah@M.Thiyagarajan, (2003)
The objective of this study is to analyze the extent to which CRM is being applied by commercial banks with regards to the SMEs. This study will analyze th erole of Relationship Managers, mode of communication between banks and the SMEs, the usage of electronic delivery channels and customers database on the retention of SME customer. This study employs the importance of personal banker model which was introduced by Colgate and Stewart (1998) and Easingwood and Arnott (1991) importance-performance analysis. two different sets of postal questionnaire were used to extract information from 136 SMEs